The best exotic Marigold Hotel [videorecording (DVD)] - Madden, John, 1949-; Dench, Judi, 1934-; Nighy, Bill, 1949-; Wilkinson, Tom, 1948-; Smith, Maggie, 1934-; Moggach, Deborah (20th Century Fox Home Entertainment, 2012)
When seven cash-strapped seniors decide to 'outsource' their retirement to a resort in far-off India, friendship and romance blossom in the most unexpected ways.